Cooperative Transmission for Satellite Wireless Sensor Networks - Yuan Lin; Yuanzhi He; Han Han (International Journal of Distributed Sensor Networks)
This paper presents the performance analysis of wireless sensor networks- (WSNs-) based satellite collocation system as cooperative transmission is applied. A scenario of satellite cluster is considered, where multiple satellites are collocated with each other. Considering that the performance of satellite systems can be improved as the spot beam is split into virtual beams, the optimized system capacity can be expected by applying the geometrical arrangement of the antennas of transmitters and receivers. In the following simulation experiments, the system capacity is investigated as various system configurations are applied. It is found that the optimal value of system capacity exists as expected, and the simulation observations are illustrated as practical limitations are considered.